Pengaruh Uang Saku, Literasi Keuangan, dan Love of Money Terhadap Manajemen Keuangan Pribadi Mahasiswa KIP-K Fakultas Ekonomika dan Bisnis Universitas Negeri Surabaya - Susanti; Anis Lestari (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
Personal financial management is the activity of managing and recording the finances of each individual used in meeting daily or future needs. The purpose of this study was to determine the effect of pocket money, financial literacy, and love of money on the personal financial management of KIP-K students at the Faculty of Economics and Business, Surabaya State University. This type of research is quantitative research. Data collection using questionnaires and tests. The research population used a limited population, namely KIP-K students at the Faculty of Economics and Business, Surabaya State University. The research sample used was purposive sampling. The research sample obtained was 98 students, with a trial of 50 students. The data was processed with the help of IBM SPSS 25 with the research instrument test, classical assumption test, and hypothesis testing.The results showed that 1) There is a significant influence of pocket money on student personal financial management, 2) There is a significant effect of financial literacy on student personal financial management, 3) There is a significant effect of love of money on student personal financial management, and 4) There is a significant effect of pocket money, financial literacy, and love of money on student personal financial management.